2019
DOI: 10.3390/rs11091014
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Land Degradation in Eastern China Grasslands with Time Series Segmentation and Residual Trend analysis (TSS-RESTREND) and GIMMS NDVI3g Data

Abstract: Grassland ecosystems in China have experienced degradation caused by natural processes and human activities. Time series segmentation and residual trend analysis (TSS-RESTREND) was applied to grasslands in eastern China. TSS-RESTREND is an extended version of the residual trend (RESTREND) methodology. It considers breakpoint detection to identify pixels with abrupt ecosystem changes which violate the assumptions of RESTREND. With TSS-RESTREND, in Xilingol (111°59′–120°00′E and 42°32′–46°41′E) and Hulunbuir (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…NDVI has negative values in the place covered by cloud, water and snow, and thus will be affected by the atmosphere (cloud, water-vapour, and aerosols). To minimize the influence of the atmosphere and of the viewing and illumination conditions, the maximum value composite (MVC) technique was developed by Holben (1986), which has been widely used in many previous studies to deal with the NDVI3g data [56][57][58][59]. In this study, MVC was used to aggregate the original biweekly NDVI series into monthly series.…”
Section: Data Sourcesmentioning
confidence: 99%
“…NDVI has negative values in the place covered by cloud, water and snow, and thus will be affected by the atmosphere (cloud, water-vapour, and aerosols). To minimize the influence of the atmosphere and of the viewing and illumination conditions, the maximum value composite (MVC) technique was developed by Holben (1986), which has been widely used in many previous studies to deal with the NDVI3g data [56][57][58][59]. In this study, MVC was used to aggregate the original biweekly NDVI series into monthly series.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Previous studies have used land degradation reflected by vegetation to monitor desertification [7][8][9] as vegetation cover is a highly unstable and delicate portion of the ecosystem [10]. Due to the biophysical response of plant respiration, evapotranspiration, and photosynthesis, vegetation has an obvious relationship with climatic factors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with similar studies [19,23,25], here, we used MOD-R to study vegetation changes in small areas. The results showed that MOD-TR had detected more pixels with a significant decrease than when using MOD-R in small areas.…”
Section: Validation Of the Mod-tr In Prdmentioning
confidence: 99%
“…TSS-RESTREND mainly employed GIMMS NDVI data (i.e., GIM-TR) to study large areas. A previous study used GIM-TR to analyze vegetation change in a relatively small study area [25], but its results showed that GIMMS NDVI was too coarse to detect enough breakpoints by BFAST, which would lead to an underestimation of the vegetation decrease. However, data from a new generation of satellites, namely Moderate Resolution Imaging Spectroradiometer (MODIS) NDVI data, with a higher resolution (i.e., 250 m, 500m and 1000m) is more commonly used to detect the vegetation change in small study areas [26][27][28].…”
Section: Introductionmentioning
confidence: 99%